Habitat associations and distribution of the hyperbenthic shrimp, Nauticaris marionis, around the sub-Antarctic Prince Edward Islands. (September 2017) - Haley, Craig; von der Meden, Charles; Atkinson, Lara; Reed, Cecile
Abstract: The association of organisms with particular habitats and habitat-forming organisms, can strongly influence species distributions, interactions and wider ecosystem services. At the sub-Antarctic Prince Edward Islands, the caridean shrimp Nauticaris marionis is a principal part of the benthic ecosystem, occurring between ca. 50 m and 600 m. Its role as a trophic link between the primary productivity and higher predators is established, but little is understood of its in situ habitat usage and associations or of how these structure patterns of abundance. We investigated these aspects directly using a benthic camera sled, sampling 27 stations between 50 m and 500 m. Substratum type was characterised, and estimates of percentage cover of the 13 main groups of habitat-forming epibenthic taxa were made, alongside absolute counts of N. marionis within 'digital quadrats' drawn from 300 m transects. The distribution of N. marionis was influenced by depth, substratum type and overall biogenic cover, being limited to habitats between 50 and 160 m depth on mud or gravel substrata only, and having > 50% biogenic cover. The presence/absence of N. marionis related to significantly different epibenthic assemblages (termed biogenic habitats), but this effect was contingent on depth. Likewise, densities of N. marionis were significantly affected by biogenic habitat type, identifying an association with two biogenic habitat groups, one dominated by red-algae, the other by structurally complex bryozoan species. These associations likely relate to the structural complexity of the two habitat groups, rather than the specific taxa involved. The apparent absence of N. marionis at depths > 160 m contrasts with earlier records and poses questions about the trophic importance of the shrimp in deeper habitats. Highlights: Optical sampling directly established habitat associations. The shrimp Nauticaris marionis requires > 50% epibenthic cover. Effect of substratum type superseded by presence of biogenic habitat. Two associations identified with: nearshore red algae and deeper bryozoans. Complex biogenic habitats may be increasingly important in deeper areas.